Effect of processing on the antioxidant content of guava (Psidium guajava L.) jam made from different cultivars - Hong, Jeysee Christine C.
ABSTRACT The antioxidant capacity of guava and processed jams were investigated. The study was divided into two phases. Phase 1 of the study was allotted for the jam formulation screening while Phase 2 was allotted for the jam processing applied to three guava cultivars, namely pink, white and yellow. The antioxidant tests conducted were Vitamin C determination by modified Loeffler and Ponting method, scavenging activity (SA) by DPPH radical scavenging assay and total phenolics content (TPC) by Folin-Cioacalteu assay. For the first phase of the study, three treatments were applied to a pink-fleshed guava. In phase I, the obtained Vitamin C content of the guava fruit was 290 mg/100 g fresh fruit while the three treatments have reduced Vitamin C content of 79.41 mg/100 g (T1), 29.74 mg/ 100 g (T2) and 78.92 mg/100 g (T3). The %inhibition of the samples were determined to be 92.43% 91.24%, 69.38%, and 89.92% for fruit, T1, T2 and T3, respectively. The reported SA of the guava fruit is at 8118 mg GAE/g dry matter. The TPC for the three treatments were determined as 2566 mg GAE /g for T1, 2469 mg GAE/g for T2 and 2229 mg GAE/g for T3. The results in the first phase of the study revealed that treatment 1 had the highest Vitamin C, TAC and TPC among the three treatments although it is not significantly different from Treatment 3. The chosen treatment which was Treatment 1, was then applied to the three different cultivars in the second phase of the study. The Vitamin C obtained from the three cultivars were 244.08 mg AA/100 g pink guava, 225.36 mg AA/100 g white guava and 302.71 mg/100 g yellow guava. The reported Vitamin C content of the guava jams were 59.61 mg AA/100 g pink guava jam, 49.75 mg/ 100 g white guava jam and 62.91 mg/100 g yellow guava jam. The %inhibition of the fruits were 90.13%, 95.09% and 93.25%, for the pink, white and yellow cultivars, respectively The %inhibition of the processed jams were 56.54%, 76.32% and 63.97%, for the pink, white and yellow cultivars, respectively. The TPC for the guava fruits were 4705 mg GAE/g, 7380 mg GAE/g, and 7708 mg GAE/g for pink, white and yellow fruits, respectively. The TPC values for the yellow cultivar were the highest among the three. The TPC for the processed jams were 1578 mg GAE/g, 2085 mg GAE/g, and 3526 mg GAE/g for pink, white and yellow guava jams, respectively. The processed jam with the highest TPC was determined to be the yellow cultivar. Thermal processing of guava fruits significantly decreased the Vitamin C content, SA and TPC. There was no single cultivar that emerged superior over the three, although the yellow cultivar had the highest TPC and Vitamin C among the group.